Early Shī'ī Thought: The Teachings of Imam Muhhiriqammad al-Bāqir - Buckley, Ron (Journal of Semitic studies, 2004)
Early Shī'ī Thought: The Teachings of Imam Muhhiriqammad al-Bāqir Arzina R.Lalani , I.B. Taurus, London 2000. 203. Price: £25.00 hardback. ISBN: 1-86064-434-1